Meningkatkan Perkembangan Sosial Anak Melalui Penerapan Model Pembelajaran Kooperatif Tipe JIGSAW Pada Kelompok B Di RA Al-Hilal (Penelitian Tindakan Kelas Pada Anak Usia 5 – 6 Tahun) - H. Suhada; Desy Apriani (UNIVERSITAS RAHARJA, 2018)
Improving Social Development of Children through the Application of Cooperative Learning Model Jigsaw Type In Group B at RA Al-Hilal (Classroom Action Research In children aged 5-6 years). This research is based on the existence of a problem related to social development of learners that is lack of sense of togetherness, mutual ownership, mutual love among friends, being indifferent and waning mutual sense of mutual cooperation among students with each other due to the process of changing the era of globalization era Involving children are more self-interested and tend not to care about the environment.Problems revealed in this research is how the application of cooperative learning model of jigsaw type can improve social development of child in group B RAAl-Hilal? The goal to be achieved in this research is to know the improvement that happened in social development through applying cooperative learning model in group B RA Al-Hilal of academic year 2016/2017.This research is a Classroom Action Research. Subjects in this study were students of group B RA Al- Hilal, second semester of the academic year 2016/2017 which amounted to 20 children with the composition of men number of 9 children and women of 11 children. Based on result of analysis of research data after getting treatment using cooperative learning model, showing the positive and significant influence of social development of children in group B RA Al-Hilal academic year 2016/2017. The score of improvement of social development of children in group B RA Al-Hilal The academic year 2016/2017, initial condition obtained the total score of 242 points (50.42%) then in cycle I the number of scores increased by 89 points (18.26%) to 331 Points (68.68%), and finally in cycle II the number of scores increased by 96 points (20.15%) to 427 points (88.83%). Therefore, it can be concluded that the application of cooperative learning model proved to improve social development of children in group B RA Al-Hilal academic year 2016/2017.